Potential Use of Emerging Technologies for Preservation of Rice Wine and Their Effects on Quality: Updated Review - Pei, Jinjin; Liu, Zhe; Huang, Yigang; Geng, Jingzhang; Li, Xinsheng; Ramachandra, Sisitha; Udeshika, Amali Alahakoon; Brennan, Charles; Tao, Yanduo (Frontiers in Nutrition, 2022)
Rice wine, a critical fermented alcoholic beverage, has a considerable role in different cultures. It contains compounds that may have functional and nutritional health benefits. Bacteria, yeasts, and fungi commonly found in rice wines during fermentation can induce microbial spoilage and deterioration of the quality during its distribution and ageing processes. It is possible to control the microbial population of rice wines using different preservation techniques that can ultimately improve its commercial shelf-life. This paper reviews the potential techniques that can be used to preserve the microbial safety of rice wines while maintaining their quality attributes and further highlighting the advantages and disadvantages of each technique.